Utilization Behavior and Frontal Lobe Lesions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Utilization behavior was investigated in an adult with an acute behavioral disturbance, memory deficits, and a localized inferior medial bifrontal lesion at the Psychology Department, National Hospital, Queen Square, London; the MRC Applied Psychology Unit, Cambridge; and Department of Neurology, Atkinson Morley's Hospital, Wimbledon; and St. Andrews Hospital, Northampton, UK.